2023
DOI: 10.7759/cureus.39615
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Body Fat Index and Gestational Diabetes Mellitus: A Prospective Cohort Study

Abstract: Background: Body mass index (BMI) has commonly been used to evaluate the risk of gestational diabetes mellitus (GDM), but BMI does not always represent body fat mass distribution. Body fat index (BFI), which includes the measurement of subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT), has been suggested to be a better predictor for GDM than BMI. Objective: The objective of this study is to compare the risk of GDM among pregnant females with BFI of >0.5 and ≤0.5. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…In addition, this study also found that excess preconception BMI is one of the factors that pose an independent risk for GDM. This is because overweight and obesity affect insulin metabolism and production, increasing the body’s need for insulin, and thus increasing the risk of GDM[ 15 ]. Therefore, weight control before pregnancy and maintaining a normal BMI can reduce the risk of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study also found that excess preconception BMI is one of the factors that pose an independent risk for GDM. This is because overweight and obesity affect insulin metabolism and production, increasing the body’s need for insulin, and thus increasing the risk of GDM[ 15 ]. Therefore, weight control before pregnancy and maintaining a normal BMI can reduce the risk of GDM.…”
Section: Discussionmentioning
confidence: 99%